Performance: Revealing the Orpheus within - Rooley, Anthony (Privately Published, 2005)
This book appeals to a wide readership: performers of all kinds, not only musicians, as well as 'the audience'. Indeed, the author argues that all of life can be experienced as a performance of some kind, and there is more to the 'performer/audience equals active/passive dynamic' than meets the eye. Using the format of the Elizabethan world view broadens the scope for enjoyment of any performance. It also makes the book interesting for readers particularly interested in this period of history, and lovers of renaissance music especially. It almost goes without saying that the work will be of interest to those who love Rooley's lute music and would like to learn more about the ideas behind it.The book is at the same time scholarly and practical. It is well-written, elegantly phrased, full of unexpected gems of ancient wisdom gleaned from many cultures as well as more mundane observations. It treats period sources with academic respect, and explains abstract concepts clearly. At the same time, it offers very practical tips and advice for concrete performances, which any performer at any level can benefit from. With Rooley's help performers can discover a new dimension in their enjoyment of performing and interacting with the audience which is at once mystically abstract and tangibly effective.
Keywords: Historically informed performance; art philosophy & esthetics